Evidence or stereotype? Health inequalities and representations of sex workers in health publications in England. (November 2020) - Putnis, Nina; Burr, Jennifer
The health of sex workers is considerably influenced by their position in society and by the marginalisation and stigmatisation they face worldwide. They are frequently criminalised and labelled as deviant, disordered or 'vulnerable': stereotypes that simplify and misrepresent their realities. Sex work policies create social and structural barriers, creating dangerous work environments and exacerbating significant health inequalities. Health organisations and their policies play an important role in highlighting inequalities and guiding health systems in reducing them. In this article, we use a document analysis design to analyse how and when sex workers are depicted in policies and publications by English national health organisations: National Health Service (NHS) England, Public Health England and the National Institute for Health and Care Excellence, along with the UK Department of Health. We find that sex workers are largely absent in these documents and, when present, are depicted not using evidence, but simplistically with moralistic undertones. The dichotomous constructions found in these texts: vulnerable yet also criminal 'prostitute' reflect wider political and social constructions of sex working women. This not only obscures their realities but also homogenises, blames and stigmatises, ultimately doing the opposite of what these organisations purport to do: it damages their health and well-being.